PENGARUH PEMANFAATAN MEDIA PEMBELAJARAN DIGITAL EDUCAPLAY TERHADAP MINAT BELAJAR PADA MATA PELAJARAN INFORMATIKA SISWA KELAS XI SMA KRISTEN CITRA BANGSA MANDIRI KUPANG - Christina Deryanti Tahu; Khatrin Juliani Taku Neno; Jhon Enstein (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
This study was motivated by the low level of students' learning interest in the Informatics subject, which was caused by conventional teaching methods and the limited utilization of interactive digital learning media. This study aimed to determine the effect of utilizing Educaplay digital learning media on the learning interest of Grade XI students at SMA Kristen Citra Bangsa Mandiri Kupang in the Informatics subject. This study employed a quantitative approach using an experimental research method with a One Group Pretest-Posttest Design. The data were analyzed using a paired sample t-test. The results showed that the average learning interest score increased from 66.83 before the treatment to 71.50 after the treatment. The hypothesis test results showed a significance value of 0.011 (< 0.05), thus Ha was accepted and H₀ was rejected. These findings confirm that there was an increase in students' learning interest scores after being given treatment using Educaplay digital learning media.